Bacteria of Dental Caries in Primary and Permanent Teeth in Children and Young Adults - Aas, Jørn A; Griffen, Ann L; Dardis, Sara R; Lee, Alice M; Olsen, Ingar; Dewhirst, Floyd E; Leys, Eugene J; Paster, Bruce J (Journal of Clinical Microbiology, 2008)
Although Streptococcus mutans has been implicated as a major etiological agent of dental caries, our cross-sectional preliminary study indicated that 10% of subjects with rampant caries in permanent teeth do not have detectable levels of S. mutans. Our aims were to use molecular methods to detect all bacterial species associated with caries in primary and permanent teeth and to determine the bacterial profiles associated with different disease states. Plaque was collected from 39 healthy controls and from intact enamel and white-spot lesions, dentin lesions, and deep-dentin lesions in each of 51 subjects with severe caries. 16S rRNA genes were PCR amplified, cloned, and sequenced to determine species identities. In a reverse-capture checkerboard assay, 243 samples were analyzed for 110 prevalent bacterial species. A sequencing analysis of 1,285 16S rRNA clones detected 197 bacterial species/phylotypes, of which 50% were not cultivable. Twenty-two new phylotypes were identified. PROC MIXED tests revealed health- and disease-associated species. In subjects with S. mutans, additional species, e.g., species of the genera Atopobium, Propionibacterium, and Lactobacillus, were present at significantly higher levels than those of S. mutans. Lactobacillus spp., Bifidobacterium dentium, and low-pH non-S. mutans streptococci were predominant in subjects with no detectable S. mutans. Actinomyces spp. and non-S. mutans streptococci were predominant in white-spot lesions, while known acid producers were found at their highest levels later in disease. Bacterial profiles change with disease states and differ between primary and secondary dentitions. Bacterial species other than S. mutans, e.g., species of the genera Veillonella, Lactobacillus, Bifidobacterium, and Propionibacterium, low-pH non-S. mutans streptococci, Actinomyces spp., and Atopobium spp., likely play important roles in caries progression.